Determinants Of Digital Wallet Adoption Among Generation Z Students In Economics Education: Faktor Yang Mempengaruhi Penggunaan Dompet Digital Di Kalangan Mahasiswa Gen Z Pendidikan Ekonomi - Dwi Herlindawati; Irmadatus Sholekhah (Jurnal Pendidikan Akuntansi Indonesia, 2026)
This study investigates the influence of digital financial literacy, lifestyle, and perceived convenience on individuals’ decisions to use digital wallets. A quantitative research design was adopted, utilizing primary data collected through online questionnaires. The sample comprised 102 students from the Economics Education Study Program at the University of Jember who actively use digital wallets, selected using a purposive sampling technique. Data analysis was conducted using SPSS version 27 through multiple linear regression analysis, supported by t-tests and F-tests. The results indicate that digital financial literacy has a significant effect on digital wallet usage (Sig. = 0.000). Lifestyle also shows a significant influence on digital wallet usage (Sig. = 0.001). Furthermore, perceived convenience significantly affects digital wallet usage (Sig. = 0.002). The t-test results confirm that all independent variables significantly influence digital wallet usage individually, while the F-test results demonstrate a significant simultaneous effect of digital financial literacy, lifestyle, and perceived convenience (Sig. = 0.000). This finding is supported by the coefficient of determination (R²) value of 0.654, indicating that 65.4% of the variation in digital wallet usage can be explained by these three variables, while the remaining variance is attributable to other factors not examined in this study.